Compressive Strength of Post Fire Exposed Concrete Column Wrapped with Fiber Reinforced Polymer - Dwi Agus Setiawan Wardaya; Handoko Sugiharto; Pamuda Pudjisuryadi (Institute of Research and Community Outreach - Petra Christian University, 2017)
In this study, behaviour of reinforced concrete columns strengthened using fiber reinforced polymer (FRP; glass fiber and carbon fiber) after fire exposure are discussed. After being exposed to fire as high as 720oC for 180 minutes, the specimens showed concrete and reinforcement strength degradation, even though there was no carbonation. It was found that specimens wrapped by carbon fiber showed better compressive strength but less ductility compared to specimens wrapped by glass fiber. It was also found that the low initial compressive strength did not decrease FRP confinement effectiveness. Increase of wrapped concrete compressive strength was evident despite the low initial strength (<17 MPa). Strength estimation using ACI 440.2R-08 formula, which is originally for wrapped plain concrete without fire heat exposure, underestimated the compressive strength. In the proposed formula, the initial compressive strength (f’co) should be adjusted by considering the modulus elasticity and strain limitation to have more precise estimation.